Svádění jako léčka diskursu: Poznámky k sedukci a produkci zdánlivého a k estetice mizení - Bystřický, Jiří (Lidé města, 2001)
Seduction as a trap of seduction means above all an indispensable consideration of a relatively significant role of simulation practices of the discourse itself. Wherever the seduction convinces us thal its signs lead to a fatal misunderstanding of the very game of seduction and indicate the ways on which to go to the imaginary chance of self-respect, the discourse offers its own, alternative and more sophisticated strategy. The signs of seduction, which eventually disappear forever, but resurface elsewhere in the same extent, thus frustrating a thorough understanding of their movement and possible sense, are somewhat comprehensively detached from their trajectories of movement if they are "forced to describe their own movement." This means to divulge a certain topography of changes. The importance of discourse strategies lies in the fact that in the moment when the signs of seduction can be „caught red-handed" as „inattentive", which means a certain inability to control the impact of its movement, these signs can be detached in a certain place and replaced by lines of complementation which are a result of a simulation practice of a discourse. This basically means that whenever the subject of a seduction game realises that a third member must be placed into the game, provided this is a dyadic game of seduction, this means his own version of a reflective monitoring of its image which is being offered to the game in order to seduce and this creates a situation complication, a state of unbalance and dispersal of seductive signs. lnstead of the signs of the seduction itself he mainly reads his own images of seduction, his self-portraits and scenic gestures for which he does not necessarilly write scenarios, but which he can be sooner or later - if they prevail - transferred and eventually deflect the signs of original seduction outside the sphere of seduction and let them disappear in the final version. It is just in this moment that the game is entered by the discourse which starts placing the lines of importance instead of the disappeared places after the original signs of seduction. These lines of importance are certainly derived from the importance of his own, cherished versions of self-image and self-portraits. However, it is absolutely necessary to find for them such lines of communication and establishment of contact which are never noticed by the other participant. If the game of discourse simulation of creating self-portrait is consequent, it always leads to the situation which is actually only rarely expected: the seduction eventually results in the absorption of discourse simulation, an absorption of a self-inflicted need to find cheap replacements for the actual and permanent image of ourselves. The price of such an image is too high to be paid for an often convincing, but still cheap simulation.